Adaptive antenna arrays and equalization techniques for high bit-rate QAM receivers. - Jind-Yeh Lee
Adaptive antenna arrays provide wireless communication systems with larger service capacity and higher link quality through frequency reuse and cochannel-interference rejection. In practice, the propagation environment is nonideal with shadowing, severe stationary, and fast multipath fading. In this paper, the combination of adaptive antenna arrays and equalization techniques is employed to achieve reliable high-bit-rate wireless communications in a multipath, multiinterferer environment. A low-complexity receiver structure is investigated for the feasibility of portable wireless communications applications. The performance of the proposed receiver is analyzed in both outdoor and indoor multipath conditions. The simulations show that, although the adaptive beamformer is capable of cancelling long-delayed multipath reflections in the outdoor environment within its degrees of freedom, the adaptive equalizer is mandatory to compensate for the residual of the outdoor environment or the short-delayed multipath reflections of the indoor environment to achieve a high-quality link and high data rate. The digital circuits of the proposed receiver are estimated to perform 50 billion operations per second (GOPS) of digital signal processing functions, and the gate count is estimated to be 100 000 for a custom integrated circuit implementation
Keywords: VLSI; Adaptive antenna arrays; Adaptive beamformer; Adaptive equalization; Cochannel-interference rejection; Custom integrated circuit implementation; Digital circuits; Digital signal processing; Fast multipath fading; Frequency reuse; Gate count; High bit-rate QAM receivers; High-quality link; Indoor multipath; Link quality; Long-delayed multipath reflections; Low-complexity receiver structure; Multiinterferer environment; Outdoor multipath; Portable wireless communications; Propagation environment; Receiver performance; Service capacity; Shadowing; Short-delayed multipath reflections; Simulations; Stationary multipath fading; Wireless communication systems